PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA PEGAWAI PADA DINAS PENGELOLAAN SUMBER DAYA AIR PROVINSI SUMATERA UTARA - Hilma Harmen; Juwita Sari Nasution (Jurnal PLANS : Penelitian Ilmu Manajemen dan Bisnis, 2015)
This study aims to identify and explain the influence of organization culture and non physical working environment of employee performance at Dinas Pengelolaan Sumber Daya Air Provinsi Sumatera Utara.The research was conducted at Dinas Pengelolaan Sumber Daya Air Provinsi Sumatera Utara with population of employers is 192 people and the sample is 66 people. Obtained the model equation multiple linear regression Y = 16,325 + 0,374X1 + 0,541X2, which means that if organization culture and non physical working environment is zero can explain the employee performance is 16,325 units.With the coefficient of value determination (R2) is 0,227 indicates that organization culture and non physical working environment can explain performance employee of 22,7 % and 77,3 % explained by other factors not included in this research.Based on the test-F obtained value of count F is 9,271 more than value of table F 3,14, it can concluded that organization culture and non physical working environment have influence simultan eously of performance employee. Based on the test-t obtained value of count t of organization culture is 2,186 more than value of table t 1,669, it can concluded that organization culture have influence partialy of performance employee. And non physical working environment have value t is 3,019 more than value table is 1,669, it can concluded that non physical working environment have influence partialy of performance employee. The result of analysis concluded in this research that organization culture and non physical working environment are significantly influence to Employee Performance at   Dinas Pengelolaan Sumber Daya Air Provinsi Sumatera Utara. Keywords : Employee Performance, Oorganization Culture, Non Physical Working       Environment